SPECTRUM OF MOLECULAR GENETIC ALTERATIONS AND DIVERSITY OF CLINICAL FORMS OF STARGARDT DISEASE - N. L. Sheremet; I. G. Grushke; N. V. Zhorzholadze; I. A. Ronzina; A. A. Mikaelyan; S. A. Kurbatov; V. V. Kadyshev; K. I. Anoshkin; V. V. Strelnikov (Сибирский научный медицинский журнал)
Purpose of the study was to assess the spectrum of molecular genetic disorders and the variety of clinical forms in patients with Stargardt disease. Material and methods. 56 patients aged 15-44 years who had been diagnosed with Stargardt disease in a history or at the time of the examination were included in the study. All patients underwent standard complete ophthalmic examination, as well as high-performance parallel sequencing of the coding sequences and adjacent areas of the introns of the ABCA4, ELOVL4, PROM1 and CNGB3 genes, as well as of the minor exons of the ABCA4 gene. Results. Mutations in one of 4 genes ( ABCA4, ELOVL4, PROM1 and CNGB3 ) were detected in 46 of 56 patients (82.1 %). An inverse correlation was found between the duration of the disease and the loss of visual acuity per year for the three groups ( k = -0.86, k = -0.93, k = -0.63, p < 0.05, respectively, with the debut of the Stargardt disease at 10 year, 11-30 year and > 31 year). A frequent mutation of the ABCA4 gene, p.G1961E was detected in 18 patients and in 83 % of cases (15 patients) is associated with a mild course of Stargardt disease. Complex mutation [p.L541P, p.A1038V] was detected in 17 patients, in 53 % (9 people) of cases was associated with more severe phenotype. However, in the compound heterozygous state with the missense mutation p.G1961E, a relatively mild course of the disease was observed. Conclusions. The loss of visual functions in Stargardt disease depends on the severity of the genetic defect in each case and on the disease’s duration in general.